2016
DOI: 10.1007/s10815-016-0838-6
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and perinatal outcome of babies born from sperm selected by MACS from a randomized controlled trial

Abstract: Purpose The purpose of this study is to assess outcomes after magnetic-activated cell sorting (MACS) technology on obstetric and perinatal outcomes compared with those achieved after swim up from randomized controlled trial. Methods This is a two-arm, unicentric, prospective, randomized, and triple-blinded trial and has a total of 237 infertile couples, between October 2010 and January 2013. A total of 65 and 66 newborns from MACS and control group, respectively, were described. Results MACS had no clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Moreover in 2017 Romany et al did a randomized control trial on 237 couples with liveborn children conceived through the association of MACS and ICSI. They concluded that there were no noticeable differences in obstetric or perinatal events when MACS is used (Romany et al 2017). However, further research is needed to verify the presence of freely floating microbeads in the annexin V (-) fraction on the plasma membrane of the spermatozoa, and long term effects on the health and development of children.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover in 2017 Romany et al did a randomized control trial on 237 couples with liveborn children conceived through the association of MACS and ICSI. They concluded that there were no noticeable differences in obstetric or perinatal events when MACS is used (Romany et al 2017). However, further research is needed to verify the presence of freely floating microbeads in the annexin V (-) fraction on the plasma membrane of the spermatozoa, and long term effects on the health and development of children.…”
Section: Discussionmentioning
confidence: 99%
“…Patients using their own oocytes, and those undergoing oocyte-donation treatment were included. Details of donor selection and work-up studies were previously reported [ 20 ].…”
Section: Experiments Sectionmentioning
confidence: 99%
“…This technique also reduces the proportion of sperm with fragmented DNA in the ejaculate before using it for ART procedures [ 19 ]. In addition, there are no clinically adverse effects at the obstetric and perinatal levels in newborns who were closely monitored following oocyte-donation and sperm-selection treatments with MACS [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that not all species are suitable for MACS separation method. In our knowledge, most of the research for MACS separation or the combination of DGC and MACS used human samples (de Vantéry Arrighi, Lucas, Chardonnens, & De Agostini, 2009;Gil, Shalom, Sivira, Carreras, & Checa, 2013;Martin et al, 2017;Romany et al, 2017). DGC has been proven to effectively remove nonviable spermatozoa.…”
Section: Discussionmentioning
confidence: 99%